Pedagogy of the Oppressed - Pereira, Patrik Sudário de Souza; Salomão, Maria Aparecida Vieira (Revista Hipótese, 2016)
Review of the book FREIRE, Paulo. Pedagogia do Oprimido. Rio de Janeiro: Paz e Terra, 2011. 50ª edição.
Keywords: Pedagogy; release; education